PENGATURAN PRINSIP “TANGGUNG JAWAB KARENA KESALAHAN” APABILA TERJADI EVENEMENT PADA PENGANGKUTAN DARAT - Bagus Suardana, I Made; Mahartayasa, Made (Kertha Semaya : Journal Ilmu Hukum, 2013)
The regulation principle of responsibility by faults in the event evenemen on landtransport. Ground transportation as the dominant tools of transport in Indonesia.Application of the laws does not regulate road traffic compensation losses suffered bythird parties in the delivery of goods by public transport. The purpose this paper, toexplain the inconsistencies by the rule in providing compensation to the third party. Themethod used in this paper studies the method by comparing the normative provisions bylaws. To obtain legal protection, peoples must pay extra of the diversion of risk.
Keywords: Transportation, Ground, Compensation, Responsibility